Nomenclatural notes in Gomesa (Oncidiinae, Cymbidieae, Epidendroideae, Orchidaceae) for the Brazilian flora - Penha, Túlio Luiz Laitano; Guimarães, Leonardo R. S. (Phytotaxa, 2017)
We propose new combinations in the genus Gomesa, to accommodate species previously assigned to Baptistonia. These are needed according to recent phylogenetic studies.